Preempting Mass Murder: Improving Law Enforcement Risk Assessments of Persons with Mental Illness - Milby, John D (Homeland security affairs, 2015)
Law enforcement officers are regularly called upon to respond to assist mentally ill persons in crisis; some experts estimate that as many as 20 percent of all law enforcement calls for service involve persons with a mental illness.[1] In the majority of communities across the country, law enforcement is the first and often the sole community resource that can be called upon to respond and address mentally ill persons in various stages of crisis.[2] A growing body of evidence now suggests that a subgroup of persons with serious mental illness—those who are psychotic, not taking their medications, or are self-medicating through substance abuse—are significantly more dangerous than aperson in the general population.[3] This places a significant public safety obligation upon law enforcement officers, as well as the duty to ensure that the mentally ill persons receive proper care and treatment for their condition. Historically, the rationale for law enforcement intervention in non-criminal situations involving mentally ill persons is derived from two common-law principles: 1) the power and authority of police to protect the safety and welfare of the community, and 2) the state’s parenspatriae duty to act on the behalf of citizens who are temporarily or permanently incapable of caring for themselves.[4] Recently, mass murders perpetrated by persons suffering from serious mental illness (SMI), including the Washington Navy Yard shooting and the Isla Vista, California shooting, have resulted in increased scrutiny of law enforcement’s role in managing mentally ill persons and also sparked a national dialogue about what can be done to prevent future incidence of violence by persons with a SMI. While mental disorders are generally widespread, with nearly one in four Americans affected, about six percent of the population (or approximately 19 million people in the United States)[5] are believed to suffer from a serious mental illness.[6]Closer analysis of the mass murders committed from January 2013 through December 2013 reveals that while are a variety of motives for mass murder, at least half of all identified perpetrators of mass murder studied in this thesissuffered from serious mental illness or were suspected by those closest to them of having serious mental disorder. milby_figure1Figure 1. Prevalence of Mental Illness among Mass Murderers, 2013 According to the FBI, the incidence mass shootings and mass murder are on the rise nationally, now averaging roughly 16 a year, up from an average of sixper year only a decade ago.[7] This places a significant responsibility upon law enforcement officers who, due to their frequent interaction with mentally ill persons, must be adequately trained and equipped to assess the potential dangerousness of this growing population. Currently, law enforcement training regarding managing mentally ill persons is limited. According to a study of 70 participating law enforcement agencies conducted in 2003, the median number of training hours for new recruits was 6.5, while the median for in-service training was a paltry one-hour of training.[8] Worse, there is no law enforcement training specific to conducting risk assessments of mentally ill persons for dangerousness, in spite of this being a routine function of law enforcement when called to assist a mentally ill person in crisis. As a result, most law enforcement assessments for dangerousness are conducted in a parochial, dichotomous manner—either there is a risk, or there is not. Where law enforcement has made progress is in the realm of behavioral threat assessments (BTAs). This is based on the work of Robert A. Fein, a clinical psychologist with the U.S.Secret Service, and Bryan Vossekuil, a special agent with the Secret Service,who conducted the Exceptional Case Study Project in the 1990s.[9] This research employed an incident focused, behavior-based approach to analyzing 83 persons known to have engaged in 73 incidents of assassination, near assassination, or attack on public officials from 1949 to 1995.[10] This research has since been applied to the problem of identifying potential school shooters with some success, and it is informative in approaching the issue of violence among the mentally ill. But BTAs differ from the violence risk assessment law enforcement is expected to conduct when dealing with a mentally ill person in crisis in regards to the goals, context, process, structure, and, most importantly, time line.[11] While law enforcement is deficient in tools and training for assessing the dangerousness or risk for violence among mentally ill persons, researchers, clinicians, and experts in the field of mental illness are not. Researchers and clinicians have established rich theoretical frameworks and benefit from decades of significant research and experience in violence risk assessments of mentally ill persons. Subsequently, clinicians have developed several validated tools for assessing the risk for violence among the mentally ill, including Hare’s psychopathy checklist, the historical, clinical risk management-20 (HCR-20), the Violence Risk Appraisal Guide (VRAG), and the vaunted McArthur Violence Risk Assessment Study (VRAS). Most importantly, as a result of this research and experience, clinicians abandoned the dichotomous “yes/no” approach to dangerousness, and instead view dangerousness as existing on a continuum. Furthermore, though clinical violence risk assessment is still an evolving field of study, what has been conclusively established is that: 1) violence does occur with some degree of frequency among persons with mental illness; 2) that persons with certain mental disorders and symptom clusters are more likely to engage in violent behavior than persons without such; and 3) mental health professionals have some success in assessing the risk for violence among persons with mental disorder.[12] Given this growing public safety problem, this research explores the current state of law enforcement training regarding the assessment of persons with mental illness, and asks whether law enforcement could adapt and apply proven clinical methods for gauging the risk for violence. This research also applied Professor Erik J. Dahl’s Theory of Preventive Action, which postulates that there are two key factors necessary to prevent an attack. First, there must be precise warning with a near tactical level of specificity, and, second, there must be a high degree of receptivity with regard to the warning signs by those in a position to act.[13]Furthermore, Dahl suggests that the best way to analyze failures to stop attacks is to compare them to successfully preempted attacks.[14] Subsequently, four sample cases were examined; two cases where attacks by mentally ill perpetrators were completed, and two where they were thwarted by law enforcement. These cases were selected because in each instance, the perpetrator had contact with law enforcement prior to violence. The purpose of considering these cases is to examine what indications of dangerousness were available at the time law enforcement officers contacted the subject and to determine if these indicators correspond with violence risk factors established by clinicians. What this research found was that in some cases, there are sufficient risk factors and warning signs of potential violence, corresponding to clinical risk factors, that law enforcement can identify and act upon in order to pre-empt violence. This research also found that in the cases of completed attacks by mentally ill perpetrators where there were sufficient risk factors present, law enforcement officers were either unaware of the risk factors or demonstrated a low level of receptivity to those factors. Conversely, in cases of thwarted attacks, law enforcement officers demonstrated a high level of receptivity to the warning signs and risk factors presented, prompting further investigation and intervention. Finally, this research explored cases where mentally ill persons perpetrated or planned violence, confirmed that there were sufficient warning signs that correspond to clinical risk factors for violence, and integrates these risk factors into a new law enforcement risk assessment instrument. This field risk assessment guide is not intended to limit officer discretion or dictate what action officers take. Instead, by synthesizing proven risk factors from clinical and BTA models, it provides a framework for conducting comprehensive, uniform risk assessments with the hope of preventing violence. This new instrument should serve as the template for law enforcement agencies nationally in moving towards the goal of preventing acts of violence by persons with mental illness. --- [1] Kevin Johnson, “Mental Illness Cases Swamp Criminal Justice System,” USA Today, July 21, 2014, accessed September 1, 2014, http://www.usatoday.com/longform/news/nation/2014/07/21/mental-illness-law-enforcement-cost-of-not-caring/9951239/ [2] Richard Lamb, Linda E. Weinberger, and Walter J. DeCuir, Jr., “The Police and Mental Health,”Psychiatric Services 53, no. 10 (2002): 1266–1271, accessed August 17, 2014, http://psychiatryonline.org/doi/abs/10.1176/appi.ps.53.10.1266 [3] Ibid. [4] Ibid. [5] Serious mental illness (SMI) is defined as (1) all cases of schizophrenia; (2) severe cases of major depression and bipolar disorder; (3) severe cases of panic disorder, obsessive-compulsive disorder, and post-traumatic stress disorder; (4) severe cases of attention deficit/hyperactivity disorder; and (5) severe cases of anorexia nervosa. Timothy A. Kelly, “A Policymaker’s Guide to Mental Illness,” The Heritage Foundation, March 7, 2002, accessed March 13, 2013, http://www.heritage.org/research/reports/2002/03/bg1522es-a-policymakers-guide-to-mental-illness [6]Ronald Kessler, Wai Tat Chiu, Olga Demler, and Ellen E. Walters,“Prevalence, Severity, and Comorbidity of Twelve-month DSM-IV Disorders in the National Comorbidity Survey Replication,